Sorghum biomass: A sustainable alternative for particleboard production - A mini review - Sutiawan, Ikmal; Sutiawan, Jajang; Surya Kusumah, Sukma; Kartikawati, Aprilia; Martha, Resa; Miftah Rahman, Mohamad (Talenta Publisher, 2025)
particleboard production, offering an eco-friendly alternative to conventionalwood-based composites. This mini-review synthesizes recent research on thechemical, physical, mechanical, and durability properties of particleboards madefrom sorghum residues, including bagasse, stalks, and leaves. Quantitativefindings show that sorghum particleboards can achieve densities ranging from0.56 to 1.25 g/cm³, modulus of rupture (MOR) up to 34.1 MPa, modulus ofelasticity (MOE) up to 5270 MPa, and internal bond (IB) strength up to 1.92 MPa,meeting the JIS A5908:2003 Type 8 standard in several cases. Moisture content(MC) and thickness swelling (TS) can be optimized to meet dimensional stabilityrequirements through pre-treatment, adhesive formulation, and pressingconditions. Chemically, sorghum biomass has moderate to high cellulose (30–46%) and hemicellulose (21–34%) contents, with lower lignin and ash levels thantypical wood, favoring bonding and composite integrity. Synthetic adhesives (UF,PF, pMDI) and natural alternatives (citric acid, maleic acid, sucrose) have beenexplored, with several formulations showing improved water resistance andbiodegradation resistance. Enhanced durability, including termite and fungalresistance, has been observed, particularly in bio-based adhesive boards.However, challenges remain in scaling production and standardizing raw materialquality. Future research should prioritize optimizing production methods andimproving sorghum-based particleboards' mechanical and durability properties,enabling their use in a wider range of applications.